Evidence flexibilization in the criminal trial: a form of epistemic injustice - Sierra Sorockinas, David (2023)
This paper aims to analyze a type of epistemic injustice in the field of criminal procedural law. The central research question is: can reverse onus in criminal trial lead to epistemic injustice? To address this question, the text will be divided into three parts. First, we examine the concept of epistemic injustice and its various modalities. Second, we present the conditions under criminal trials in an epistemic setting. We characterize the criminal trial in an epistemological key. Finally, in third place, we present why a change in the institutional design (the burden of proof) leads to epistemic injustice.